A feasible method to improve the protection ability of metal by functionalized carbon dots as environment-friendly corrosion inhibitor. (10th August 2020) - Ye, Yuwei; Zhang, Dawei; Zou, Yangjun; Zhao, Haichao; Chen, Hao
Abstract: A green inhibitor of N-doped carbon dots (N-CDs) was obtained from the reaction between citric acid and L-histidine. Then, a series of professional equipment was selected to evaluate their structure and corrosion protective behaviors in HCl solution. Quantum chemistry and molecular dynamics were chosen to discuss the inhibition mechanism of N-CDs. Electrochemical results showed that the N-CDs exhibited super corrosion protection to metal because it could form dense and ordered adsorption film on metal surface. Compared with citric acid and L-histidine inhibitors, the inhibition efficiency of N-CDs was more than 90% at 100 mg L −1 . Based on the calculation of quantum chemistry and molecular dynamics, the low energy gap (Δ E = 0.0680 eV) and high binding energy ( E binding = 190.85 kJ⋅mol −1 ) of N-CDs indicated the strong chemisorption on metal substrate, which fully explained the inhibition mechanism of N-CDs at molecular/atomic level.